2021
DOI: 10.3389/fimmu.2020.610492
|View full text |Cite
|
Sign up to set email alerts
|

Role of the NLRP3 Inflammasome: Insights Into Cancer Hallmarks

Abstract: In response to a variety of stresses, mammalian cells activate the inflammasome for targeted caspase-dependent pyroptosis. The research community has recently begun to deduce that the activation of inflammasome is instigated by several known oncogenic stresses and metabolic perturbations; nevertheless, the role of inflammasomes in the context of cancer biology is less understood. In manipulating the expression of inflammasome, researchers have found that NLRP3 serves as a deterministic player in conducting tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 110 publications
(152 reference statements)
0
29
0
1
Order By: Relevance
“…It has been shown that the inflammasome receptor NLRP3 recognizes a diverse set of pro-inflammatory stimuli including metabolites that are actively secreted in an extracellular microenvironment during cancer expansion. These include ATP, which can activate NLRP3 inflammasome via the purinergic P2 × 7 receptors and, specifically in prostate tissue, uric acid, crystals, and infections, which have all been involved in prostate cancer progression [19].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown that the inflammasome receptor NLRP3 recognizes a diverse set of pro-inflammatory stimuli including metabolites that are actively secreted in an extracellular microenvironment during cancer expansion. These include ATP, which can activate NLRP3 inflammasome via the purinergic P2 × 7 receptors and, specifically in prostate tissue, uric acid, crystals, and infections, which have all been involved in prostate cancer progression [19].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, inflammasome seem to play a crucial role. Its activation has been indeed connected to all the hallmarks of cancer [19]. For example, NLRP3 inflammasome activation in tumor cells supports a chronic inflammatory microenvironment, which promotes malignant transformation and suppress local immunity [19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations